Marketing models as a tool for SMES in Mexico - Martínez-Moreno, Omaira Cecilia; Mondragón-Hernández, Gabriela (EFIM Ediciones, 2020)
This article analyses the basic marketing models as a tool for the development of a marketing plan for SMEs in Mexico, considering the four basic concepts of Product, Price, Place and Promotion, and the challenges it represents for its application since the birth and development of this business model, which are well known to have a high rate of disappearance in Mexico, and without forgetting that entrepreneurs can fnd in the marketing mix a faster placement of their products or services, and what every company is looking for which is the proftability of the business and permanence in the market.